REPRESENTASI KETERASINGAN TERHADAP LINGKUNGAN DALAM LAGU LAST ROAR (2019) KARYA TUAN TIGABELAS - Jena Sinanda (Universitas Sebelas Maret, 2023)
In Indonesia, the existence of tigers in the Sumatra Forest is threatened because of industrialization, which destroys the balance of nature and impacts the tiger habitat. Tuan Tigabelas is one of the Indonesian singers who used the song,